2011
DOI: 10.21273/hortsci.46.9.1282
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Treatment and Pre-processing Storage Reduce Browning Development in Fresh-cut Potato Slices

Abstract: Enzymatic browning is a serious quality limitation for fresh-cut potato (Solanum tuberosum L.) that has been successfully controlled by heat treatment in other commodities. The use of brief heat treatments with 55 °C water (HW) applied to ‘Russet Burbank’ tubers for 10, 20, 30, or 40 min before cutting was evaluated for potential implementation to control tissue browning. After heat treatment, tubers were held at 20 °C for 0 or 1 day before peeling and slicing. Control tubers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(54 reference statements)
3
18
1
Order By: Relevance
“…A good correlation between all color parameters and discoloration score was reported earlier by Tsouvaltzis et al . (), contrary to Thybo et al . () who found a good correlation only between L * and a * for peeled potatoes and Rocha and Morais () who reported that browning intensity correlated better with a * than L * values of fresh‐cut apples.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…A good correlation between all color parameters and discoloration score was reported earlier by Tsouvaltzis et al . (), contrary to Thybo et al . () who found a good correlation only between L * and a * for peeled potatoes and Rocha and Morais () who reported that browning intensity correlated better with a * than L * values of fresh‐cut apples.…”
Section: Resultscontrasting
confidence: 68%
“…Browning severity was similar in untreated ‘Russet Burbank’ potato slices stored for 6 days at 5C in an earlier study (Tsouvaltzis et al . ). Further acidification of the 0.5% citric acid solution slightly reduced the discoloration score (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The former treatment is currently the most common in the fresh-cut industry. Several studies have investigated the application of heat treatments by dipping for quality retention and safety control to replace the use of chemical treatments in fresh-cut carrot (Alegria et al, 2012), melon , broccoli florets (Moreira et al, 2011), potato (Tsouvaltzis et al, 2011), mango (Djioua et al, 2010), peach (Steiner et al, 2006;Koukounaras et al, 2008) and kiwifruit (Beirão-da-Costa et al, 2008). In general, temperatures used for hot water dips on different fresh-cut products can range from 40 to 60 C, while dipping duration ranges from a few seconds to many minutes (up to 70 min).…”
Section: Washing Sanitation Systems and Processing Aidsmentioning
confidence: 99%